PECULIARITIES OF VASCULO-ENDOTHELIAL GROWTH FACTORS’ SYSTEM IN PHYSIOLOGICAL PREGNANCY IN DEPENDENCE ON FETAL SEX - T. L. Botasheva; V. A. Linde; N. V. Ermolova; O. D. Sargsyan; N. A. Rogova (Медицинский вестник Юга России, 2013)
Purpose: To investigate the peculiarities of vasculo-endothelial growth factors’ system in physiological pregnancy in dependence on fetal sex.Material and Methods: We studied 107 women with physiological pregnancy, 52 with male fetuses, 55 with female. We studied the levels of vasculo-endothelial growth factor, placental growth factor, endothelial growth factor, endothelin-1, tumor necrosis factor-a levels in women in 1, 2 and 3 trimesters of pregnancy in dependence on factor “fetus sex”.Results: We revealed significant differences of these indices in women with male and female fetuses in dependence on gestational age. We detected significant differences in the function of vasculo-endothelial growth factors’ system in dependence on fetal sex, indicating the existence of systemic preconditions to its anatomical and functional heterochronys.Summary: There is a certain ratio of the absolute levels of the studied polypeptides in physiological pregnancy for each trimester. There were significant differences in their levels of sex of the fetus